Measuring cereblon as a biomarker of response or resistance to lenalidomide and pomalidomide requires use of standardized reagents and understanding of gene complexity. (28th October 2013) - Gandhi, Anita K.; Mendy, Derek; Waldman, Michelle; Chen, Gengxin; Rychak, Emily; Miller, Karen; Gaidarova, Svetlana; Ren, Yan; Wang, Maria; Breider, Michael; Carmel, Gilles; Mahmoudi, Afshin; et al.
Summary Cereblon, a member of the cullin 4 ring ligase complex (CRL4), is the molecular target of the immunomodulatory drugs (IMiDs) lenalidomide and pomalidomide and is required for the antiproliferative activity of these agents in multiple myeloma (MM) and immunomodulatory activity in T cells. Cereblon's central role as a target of lenalidomide and pomalidomide suggests potential utility as a predictive biomarker of response or resistance to IMiD therapy. Our studies characterized a cereblon monoclonal antibody CRBN65, with high sensitivity and specificity in Western analysis and immunohistochemistry that is superior to commercially available antibodies. We identified multiple cereblon splice variants in both MM cell lines and primary cells, highlighting challenges with conventional gene expression assays given this gene complexity. Using CRBN65 antibody and TaqMan quantitative reverse transcription polymerase chain reaction assays, we showed lack of correlation between cereblon protein and mRNA levels. Furthermore, lack of correlation between cereblon expression in MM cell lines and sensitivity to lenalidomide was shown. In cell lines made resistant to lenalidomide and pomalidomide, cereblon protein is greatly reduced. These studies show limitations to the current approaches of cereblon measurement that rely on commercial reagents and assays. Standardized reagents and validated assays are needed to accurately assess the role of cereblon as a predictive biomarker.